Light-curing dental resin-based composites: How it works and how you can make it work - David C. Watts (Frontiers Media S.A., 2023)
AimClinicians may become quite familiar with the rapid transformation of composite pastes to rigid solids as a routine phenomenon in operative dentistry. But they may still lack scientific understanding of how and why this happens. Efforts to learn scientifically about the interaction between light beams and resin-composites can significantly promote effective clinical placement of restorations. Neglect of such study can result in practical procedures of light curing that are inadequate or even seriously defective.MethodThis review addresses the underlying science and technology to elucidate how light curing works for dental resin-based composites, including-but not limited to-bulk fill types. This involves questions concerning: (a) the particle-wave understanding of light; (b) how photons can penetrate sufficiently deeply into bulk fill composites; (c) the necessary technology of LED light-curing units (LCUs); (d) the criteria for absorption of photons by photoinitiators to initiate free-radical addition polymerisation.ConclusionsThe implications for clinical practice are surveyed. These include design variables and selection criteria for LED-LCUs and guidelines on their use. This is to guide practitioners towards safe and effective light-curing procedures so that they can achieve optimal result for their patients.